Distribution of Pyroclastic Deposits around Lake Maninjau Agam District, West Sumatera, Indonesia based on Magnetic Susceptibility - Putra, Shandiyano; Rifai, Hamdi; Fadila, Riyan; Ningsih, Ella Destari; Putra, Rizaldi (Trends in Sciences, 2022)
Lake Maninjau is an erupting volcano in West Sumatra Province. The results of the eruption have now settled in various places and scattered in all directions due to the transportation process. The process of transporting volcanic material is caused by several factors such as wind and rain. This study aims to analyze the distribution pattern of volcanic material that is scattered around Lake Maninjau, Agam Regency. We have 25 types of samples divided into 3 categories. There are pumice, lava, and ash. This research was conducted at the FMIPA UNP Laboratory using the rock magnetization method. In this study, a Bartington MS2 with MS2B sensor was used by calculating the magnetic susceptibility value based on the mass of the sample. The results of the magnetic susceptibility analysis obtained varied between 74.7×10-8 - 3956.7×10-8 m3/kg which is included in the ilmenite (FeTiO3) group. The highest value of vulnerability was 2800×10-8 - 4000×10-8 m3/kg found at the core of Lake Maninjau ± 5.0 km seen from the green contour map. The lowest magnetic susceptibility values ​​0 - 800×10-8 m3/kg were found in the western part of Lake Maninjau and the material was deposited at a distance of ± 13 km from the core of the Maninjau caldera. Deposits were also found in the eastern part of Lake Maninjau ± 22.4 km from the core of Lake Maninjau and to the Middle East ± 23 miles from the core of the Maninjau caldera. The white color represents 1600 - 2000×10-8 m3/kg which is included in the moderate magnetic susceptibility value, which is ± 4 km to the southeast of the Maninjau caldera. The benefit that can be taken from this research in the ink industry is the presence of a magnetic mineral distribution map based on suseptibility values ​​and makes it easier to find raw materials for making ink around Lake Maninjau. HIGHLIGHTS Lake Maninjau stores various elements contained in the released material. The elements that make up magnetic minerals are Fe, Si, Ca, Al, K, Ti. The collection of several elements forms the raw magnetic mineral Volcanic material contains the mineral ilmenite which in theory can be used as a raw material for making TiO2 pigments, ferrous metals and chemical compounds containing iron. In the industrial field TiO2 is widely used as a paint pigment, additives in the paper-making process, ceramic raw materials, pharmaceutical industry raw materials and TiO2 is also widely used for photoclinic materials Superparamagnetic minerals are present in volcanic rock samples resulting from an eruption, the magnetic sensibility values at high frequencies are slightly lower than the magnetic susceptibility values at low frequencies. If there are no superparamagnetic minerals (SP) It can be assumed that the ancient volcanic eruptions of Maninjau belong to the type of plinia eruption which is highly exposed from magma with high viscosity or acid magma, the composition of the magma is andesitic to rhyolitic GRAPHICAL ABSTRACT